Pengembangan Modul Ajar Berbasis Project Based Learning dan Kearifan Lokal Materi Fotosintesis Kelas IV SD - Annisa Larasati; Nur Ngazizah; Titi Anjarini (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aimed to develop a Project Based Learning (PjBL) teaching module integrated with local wisdom for fourth-grade elementary school students. The main problem underlying this research was students’ high level of misconceptions about the photosynthesis concept, mostly caused by theoretical instruction without practical experiences to demonstrate the process. The module was designed to encourage active student engagement and help them understand photosynthesis through contextual experiences related to local culture. This research employed the Research and Development (R&D) method using the ADDIE model, covering analysis, design, development, implementation, and evaluation stages. Validation results indicated an average score of 4.55 (91.07%), classifying the module as highly valid. Practicality tests produced responses from teachers categorized as very practical (88.06%) and students as practical to very practical (79.58-85.7%). Effectiveness tests showed learning improvement with N-Gain values of 0.67 in the limited trial (moderately effective) and 0.72 in the broad trial (highly effective). Based on these findings, the PjBL and local wisdom-based teaching module was deemed feasible, practical, and effective for elementary science learning and holds potential for wider application to enhance learning quality and student engagement.